Crime and terrorism - Grabosky, Peter N. 1945-
Veteran researchers Grabosky and Stohl draw on organised crime to illuminate the neglected terrain between terrorism and more ordinary forms of illegal behaviour
Keywords: Crime; Terrorism; Organisiertes Verbrechen; Kriminalität; Terrorismus; Staat